Können frauen genies werden ?La catégorisation genrée des écrivaines dans le champ de la modernité intellectuelle et littéraire germanophone - Alexia Rosso (Les Cahiers de Framespa)
This article uses gender as a category of analysis to examine the writing of literary history in German-speaking modernity, based on two German cultural magazines published at the turn of the 19th and 20th centuries: Die Gesellschaft and Freie Bühne für modernes Leben/Neue Deutsche Rundschau. Based on these two media sources, I wish to evaluate how the conception of gender relations, which was at the time predominantly differentialist, may have informed the ways in which women writers were categorized in the literary field between 1890 and 1902. When placed in the historical and ideological context in which they were published, these magazines enable us to know which different visions of gender relations were prevalent among German educated elite (Bildungsbürgertum) at the time, and therefore reflect the instituting dimension of these visions in the categorization of women writers during this period.